The Effect of Organizational Culture on Teacher Performance at Mts Al-Manshuriyah, Sukabumi Cityabumi City - Neneng Neneng; Kun Nurachadijat (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
This study aims to explore the effect of organizational culture on students' learning motivation at MTs Al-Mansuriyah. The method used in this research is qualitative research with the type of field research. The research respondents consisted of 6 teachers and 20 students who were at MTs Al-Mansuriyah. This research was conducted using in-depth interviews and participatory observation as data collection instruments. Through in-depth interviews, teachers and students were interviewed to gain an in-depth understanding of the school's organizational culture and its influence on student learning motivation. Participatory observation is carried out to gain direct understanding of learning activities and interactions between teachers and students. The results of this study will be analyzed qualitatively using a thematic approach. The findings from this study are expected to provide a better understanding of how the organizational culture at MTs Al-Mansuriyah influences student motivation. The implications of this research are expected to be used as a basis for increasing a positive organizational culture at MTs Al-Mansuriyah so that it can further motivate students to learn. By gathering information from the perspectives of teachers and students, this research is expected to provide a more comprehensive understanding of the influence of organizational culture on student learning motivation at MTs Al-Mansuriyah. This research can also contribute to the development of educational strategies and policies aimed at increasing students' motivation to learn in these schools. The results showed that organizational culture was in the good category, in terms of the five indicators, namely innovation, stability, people orientation, result orientation, being calm, student learning motivation was in the good category, in terms of the five indicators, namely the desire to succeed, the drive to needs in learning, hopes and aspirations for the future, interesting activities in learning and a conducive learning environment. Keywords: Culture, Motivation, Organizational